SISTEM PENYIRAMAN OTOMATIS BERDASARKAN SUHU RUANG DAN KELEMBAPAN TANAH BERBASIS FUZZY LOGIC - Rahmalia Syahputri; Alexander Hendra Wijaya; Nurfiana Nurfiana; Dodi Yudo Setyawan (Jurnal Informatika, 2022)
Optimization of agriculture can be done by modernizing agricultural processes through the use of the Internet of Things. One of the problems with modern agricultural processes in greenhouses is maintaining stable room temperature and soil moisture conditions. Currently, automatic watering is only carried out with a scheduling system based on certain times, such as morning and evening. Based on observations of two gardens, the condition of some plants looks dry and wilted due to lack of watert. Therefore, it is essential to have a system that calculates soil moisture content and room temperature, which will then provide the results of these calculations to turn on the plant watering device. Fuzzy logic is used to determine the condition of the system that will send a signal to the IoT hardware to carry out the process of watering plants automatically by paying attention to air temperature and soil humidity. This rule is applied to the Smart Farming application, called Tani Cerdas, which is built based on Android to manage modern agriculture based on the IoT. The test showed result that the built automation system can produce a good response based on data from sensors.